Cardiovascular Reactivity in Patients With Major Depressive Disorder With High- or Low-Level Depressive Symptoms: A Cross-Sectional Comparison of Cardiovascular Reactivity to Laboratory-Induced Mental Stress. (March 2016) - Wang, Mei-Yeh; Chiu, Chen-Huan; Lee, Hsin-Chien; Su, Chien-Tien; Tsai, Pei-Shan
Depression increases the risk of adverse cardiac events. Cardiovascular reactivity is defined as the pattern of cardiovascular responses to mental stress. An altered pattern of cardiovascular reactivity is an indicator of subsequent cardiovascular disease. Because depression and adverse cardiac events may have a dose-dependent association, this study examined the differences in cardiovascular reactivity to mental stress between patients with major depressive disorder (MDD) with high depression levels and those with low depression levels. Moreover, autonomic nervous system regulation is a highly plausible biological mechanism for the pattern of cardiovascular reactivity to mental stress. The association between cardiovascular reactivity and parameters of heart rate variability (HRV), an index for quantifying autonomic nervous system activity modulation, was thus examined. This study included 88 patients with MDD. HRV was measured before stress induction. The Stroop Color and Word Test and mirror star-tracing task were used to induce mental stress. We observed no significant association between depressive symptom level and any of the cardiovascular reactivity parameters. Cardiovascular reactivity to mental stress was comparable between patients with MDD with high-level depressive symptoms and those with low-level depressive symptoms. After adjusting for confounding variables, the high-frequency domain of HRV was found to be an independent predictor of the magnitude of heart rate reactivity (β = −.33, p = .002). In conclusion, the magnitude of cardiovascular reactivity may be independent of depression severity in patients with MDD. The autonomic regulation of cardiovascular responses to mental stress primarily influences heart rate reactivity in patients with MDD.